Nuclear morphometry and chromatin textural characteristics of basal cell carcinoma - Mendaçolli, Paola Jung [UNESP]; Schmitt, Juliano Vilaverde [UNESP]; Miot, Hélio Amante [UNESP]; Brianezi, Gabrielli [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (FapUNIFESP (SciELO), 2015)
Histological subtypes of basal cell carcinoma have biological, evolutionary and distinct prognostic behavior. The analysis of characteristics of the nucleus can provide data on their cellular physiology and behavior. The authors of this study evaluated nuclear morphological parameters and textural patterns of chromatin from different subtypes of basal cell carcinoma: nodular (n=37), superficial (n=28) and sclerodermiform (n=28). The parameters were compared between neoplasms’ subtypes and with unaffected adjacent basal epithelium. Nuclear area and diameter of sclerodermiform neoplasms were superior to the other subtypes. Chromatin’s color intensity and fractal dimension were less intense in superficial subtypes. Nuclear roundness and chromatin’s entropy presented lower values in tumors than in normal epithelium. There was significant correlation between morphological and textural variables of normal skin and tumors. Morphometric elements and textural chromatin’s homogeneity of basal cell carcinomas may be related to evolutionary, biological and behavior particularities related to each histotype.
Keywords: Basal cell; Carcinoma; Chromatin; Computer-assisted; Image processing; Karyometry; Prognosis